Dementia in Latin America: Epidemiological Evidence and Implications for Public Policy - Custodio, Nilton; Wheelock, Ana; Thumala, Daniela; Slachevsky, Andrea (Frontiers in Aging Neuroscience, 2017)
Population aging is among the most important global transformations. Today, 12% of the world population is age 60 and over and by the middle of this century this segment will represent 21.5%. The increase in the population aged 80 an over, also referred to as the “oldest old” or the “very elderly”, will be even more pronounced, going from 1.7% of the population to 4.5% within the same period. Compared to European and North American countries, Latin America is experiencing this unprecedented demographic change at a significantly faster rate. Due to demographic and health transitions, the number of people with dementia will rise form 7.8 million in 2013 to over 27 million by 2050. Nowadays, the global prevalence of dementia in Latin America has reached 7.1%, with Alzheimer's disease being the most frequent type. This level is similar to those found in developed countries; however, the dementia rate is twice as high as that of the 65 - 69 years age group in developed countries. In addition, the prevalence and incidence of dementia is higher among illiterate people. Mortality rates due to dementia have risen considerably, while survival rates have decreased. The burden and costs of the disease are high and must be covered by patients' families. The prevention of dementia and the development of long-term care policies and plans for people with dementia should be urgent priorities in Latin America, considering the similarities and differences within the Region.